An analysis of teachers' pedagogical and professional competencies in the 2013 Curriculum with the 2017-2018 revision in Accounting subject - Cipto Wardoyo; Yogi Dwi Satrio; Devi Aprilia Ratnasari (REID (Research and Evaluation in Education), 2020)
Professional teachers are those who understand the four competencies, including pedagogical, professional, personality, and social competencies. This study is aimed at explaining two of the four competencies, which are pedagogical and professional competencies in the implementation of the 2013 Curriculum with the 2017-2018 revision in the Accounting subject. The approach used was qualitative with case study research at the State Vocational High School 1 Kraksaan Probolinggo. The results of the study show that teachers understand pedagogical and professional competencies by applying learning strategies and methods that are relevant to students’ characteristics, integrating strengthening character education (penguatan pendidikan karakter or PPK), Literacy, high order thinking skills (HOTS), and 21st-century skills and the materials presented are in accordance with the core competencies/basic competencies and the indicator of competency achievement presented in the lesson plans.